209k views
14 votes
Anybody knows the answer real quick

Anybody knows the answer real quick-example-1
User Etherealm
by
5.8k points

2 Answers

7 votes

Answer:

Number 2 is the answer.

Explanation:

Use the formula: y - y1 = m(x - x1)

y - 1 = -3/2(x - 2)

y - 1 = -3/2x + 3

+1 +1

y = -3/2x + 4

User Tim Duncklee
by
6.2k points
12 votes

Answer:

I think it's 3

Explanation:

To calculate the gradient equals to

y(1)-y(2)

-----------

x(1)-x(2)

So - 5 - 1 = - 6

6 - 2 = 4

-6 - 3

--- = ----- x

4 2

And the first y intercept is 1 so I guess it's 3.

Just for refernece, not sure if I'm correct. Sry

User YoungDinosaur
by
5.5k points